Improving the Motivation and Discipline of the TNI Skomlek Personnel towards the Advancement of Digital Literacy at the TNI Skomlek - Prio, Deddy; Lestari, Amin; Samsuarki, Samsuarki (JURNAL EKBIS, 2023)
The purpose of this research is to describe and explain how the motivation and discipline of Skomlek TNI personnel in managing digital archives. In triangulation of interview data using NVivo 12 Plus tools and SWOT analysis methods are used to determine strategies to increase motivation and discipline of TNI Skomlek personnel in digital archive management. From the results of the study, it is known that the work motivation of Skomlek TNI personnel in managing the Archive Digitization system is influenced by internet services that often drop out. The leadership of Skomlek TNI has tried to increase motivation by fulfilling needs such as physiological needs, security needs, social needs, esteem needs and actualization needs. Personnel discipline can be influenced by the presence of personnel at the morning assembly, the obedience of personnel to the rules and orders of superiors, and the sense of responsibility of personnel to the tasks carried out. The lack of personnel and some who are nearing retirement age and the lack of personnel mastery can affect the management of the TNI Skomlek Archives Digitization system.